Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan Pada Hotel Sinar Kabor Maumere - Renaldus Moat Minggo Da Lopes; Yoseph Darius P. Rangga; Nunsio Handrian Meylano (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research aimed to (1) determine the influence of service quality on customers satisfaction at Hotel Sinar Kabor Maumere, (2) know the influence of price on customers satisfaction at Hotel Sinar Kabor Maumere, and (3) know the influence of service quality and price on customer satisfaction at Hotel Sinar Kabor Maumere. The results of the descriptive analysis showed that the respondents’ perceptions of the service Quality variable (X1) were 71.0 with the “Good” category. Furthermore, the respondents’ perception of the price variable was 71.6 with the “Good” category. Likewise, the respondents’ perception of the consumer Satisfaction variable (Y) was 85.6 with the “very Good” category. The t-test results showed that the service quality variable had a significant value of 3.990 > 1.98761. The value of t-count > t-table, so H0 was accepted and Ha was rejected, which means that service Quality (X1) had a significan influence on Customer Satisfaction (Y). The T-test showed that the price variable (Y) had a substantial value of -.150 > 1.98761. t-count > t-table, so H0 was rejected and Ha was accepted which means that price (X2) had no significant influence on Customers Satisfaction (Y). The Service Quality variables (X1) and price (X2) had a simultaneous and significant influence on Customer Satisfacion (Y). The correlation value (r) was 0.300, this value was located between the coefficient interval 0.200-0.399 so the level of relationship between the independent variables and Consumer Satisfacion (Y) was interpreted as low.